Hope the answer helps you!!!
:)
Answer:
0
Step-by-step explanation:
Write out the 2 equations:
2x + y = -3
-2y = 6+4x
-You then pick a variable that you want to solve for. I chose to solve for y because it would be a bit easier.
-2y = 6 + 4x
-Divide both sides by -2 to isolate the variable
(-2y) / -2 = (6 + 4x) / -2
-it comes out to y = -3 -2x
-Now that you have the y you can plug in the value into the second equation.
2x + y = -3 ---> 2x + (-3 -2x) = -3
This can be simplified to:
2x - 3 - 2x = -3
The 2x's cancel out because there is a +2x and a -2x. You are left with a
-3 = -3. If you add 3 to both sides of the equation you end up with 0 = 0, which can be simplified to just 0.
Answer:
ok who are 38 no butplease
Answer: Jennifer didn't randomly assign participants to the control and experimental group.
Step-by-step explanation: In the scenario discussed above, Jennifer failed to perform a random assignment of the participants who took part in the survey, that is the experimental group, those who receive the treatment and the control group, those who don't. Random assignment is required in other to address the issue of bias in our experiment. She was supposed to perform a random assignment of the participants to the two groups instead of asking them to make a choice.
Answer:
I think it is 130 but I could be wrong... BUT I LOVE GOLF!!!